Correction: Starkute et al. Characteristics of Unripened Cow Milk Curd Cheese Enriched with Raspberry (Rubus idaeus), Blueberry (Vaccinium myrtillus) and Elderberry (Sambucus nigra) Industry By-Products. Foods 2023, 12, 2860 - Vytaute Starkute; Justina Lukseviciute; Dovile Klupsaite; Ernestas Mockus; Jolita Klementaviciute; João Miguel Rocha; Fatih Özogul; Modestas Ruzauskas; Pranas Viskelis; Elena Bartkiene (Foods)
With this Correction the journal’s Editorial Office and Editorial Board are jointly issuing a resolution to the Expression of Concern [...]